Vertical ridge augmentation using a porous composite of uncalcined hydroxyapatite and poly-DL-lactide enriched with types 1 and 3 collagen - Norio Akino; Noriko Tachikawa; Takayuki Miyahara; Reo Ikumi; Shohei Kasugai (SpringerOpen, 2019)
Abstract Background Previous studies have shown that porous composite blocks containing uncalcined hydroxyapatite (u-HA; 70 wt%) with a scaffold of poly-DL-lactide (PDLLA, 30 wt%) are biodegradable, encourage appropriate bone formation, and are suitable for use as a bone substitute in vertical ridge augmentation. The present study aimed to accelerate osteogenesis in vertical ridge formation by adding types 1 and 3 collagen to the u-HA/PDLLA blocks and assessing the effect. Material and methods The bone substitute in the present study comprised porous composite blocks of u-HA (70 wt%) with a PDLLA (27-29 wt%) scaffold and enriched with types 1 and 3 collagen (1.7 ~ 3.4 wt%). The control blocks were composed of u-HA (70 wt%) and PDLLA (30 wt%). The materials were formed into 8-mm diameter, 2-mm high discs and implanted onto the cranial bones of six rabbits. The animals were sacrificed 4 weeks after implantation, and histological and histomorphometrical analyses were performed to quantitatively evaluate newly formed bone. Results New bone formation occurred with both block types, showing direct contact with the original bone. Mean ± standard deviation bone formation was significantly greater in the experimental blocks (25.6% ± 4.8%) than in the control blocks (17.0% ± 4.7%). Conclusions Histological and histomorphometrical observations indicated that new bone was formed with both block types. The u-HA/PDLLA block with types 1 and 3 collagen is a more promising candidate for vertical ridge augmentation than the u-HA/PDLLA alone block.